A198 EOSINOPHILIC ESOPHAGITIS WITH STRICTURE PRESENTING SHORTING AFTER INITIATION OF ORAL PEANUT IMMUNOTHERAPY. (26th February 2020) - Al Yaarubi, Z; Foster, A; Avinashi, V; Lam, G; Soller, L; Chan, E
Abstract: Background: Oral immunotherapy (OIT) is increasingly practiced outside of research settings with reasonable success (Soller 2019). With OIT, a patient eats their food allergen daily, gradually increasing the dose, with the goal to prevent or reduce the severity of an anaphylactic reaction. One of the described adverse events of OIT is a risk of developing Eosinophilic Esophagitis (EoE), with cited frequency of 2.7% (Lucendo 2014). In addition, OIT is typically contraindicated in patients with known EoE but patients are not routinely screened for EoE prior to initiation of OIT. Aims: To present a case of a 12 year old boy with peanut anaphylaxis who developed eosinophilic esophagitis and an esophageal stricture shortly after starting peanut immunotherapy Methods: Patient chart review was conducted. A literature review was done using the words "eosinophilic esophagitis" and "immunotherapy". Results: A12 year old boy with asthma, allergic rhinitis and multiple anaphylactic food allergies, started peanut OIT with an allergist. Prior to OIT, the patient had no symptoms suggestive of EoE such as dysphagia, heartburn, chest pain or washing of food. Approximately 3.5 weeks into treatment, the patient developed daily vomiting. The patient was advised to stop the peanut OIT three days after symptom onset, but the vomiting continued for another 8 days. By the time of endoscopy (16 days after onset of vomiting), the vomiting had completely subsided for the previous five days. The upper GI endoscopy demonstrated signs of EoE throughout the length of the esophagus. In the mid esophagus there was resistance where the 9.8 mm gastroscope was unable to pass. A smaller gastroscope with a 5.9 mm width was easily able to pass through the stricture. Histology showed marked eosinophilia throughout the esophagus with basal cell hyperplasia, spongiosis, superficial microabscesses and stromal fibrosis consistent with EoE. The patient continued to be 'asymptomatic' at the time of endoscopy and after despite the presence of a stricture. After discussion, the patient was started on oral viscous budesonide (OVB) 1mg PO BID. The patient was re-scoped 4 weeks into OVB therapy with complete resolution of the stricture with neither macroscopic nor histologic findings of EoE. Patient is now off OVB for over a month, remains asymptomatic, and will undergo repeat endoscopy in the upcoming month to ensure normal histology Conclusions: This is the first case describing EoE with an esophageal stricture shortly after initiation of OIT. Pediatric Gastroenterologists need to be increasingly aware that patients undergoing OIT are at an increasing risk of 'developing' or at least 'unmasking' EoE. More research is required to evaluate whether EoE screening, by symptom questionnaire or endoscopy is warranted prior to beginning OIT, and whether OIT is truly needed. Upper GI endoscopy showing signs of EoE and an esophageal stricture Funding Agencies: CAG